Bone single-photon emission computed tomography/computed tomography in cancer care in the past decade: a systematic review and meta-analysis as well as recommendations for further work - Mohd Rohani, Mohd Fazrin; Zanial, Ahmad Zaid; Suppiah, Subapriya; Khor, Phay Phay; Mohamed Aslum Khan, Farahnaz; Mohamad Najib, Fatin Hayyani; Mohd Noor, Noramaliza; Arumugam, Manohar; Amir Hassan, Siti Zarina; Vinjamuri, Sobhan (Lippincott, Williams & Wilkins, 2021)
Skeletal whole-body scintigraphy (WBS), although widely used as a sensitive tool for detecting metastatic bone disease in oncology cases, has relatively low specificity. Indeterminate bone lesions (IBLs) detected by WBS cause a diagnostic dilemma, which hampers further management plans. In the advent of hybrid imaging, single-photon emission computed tomography/computed tomography (SPECT/CT) has been gaining popularity as a tool to improve the characterisation of IBLs detected by WBS. As yet, there has not been a systematic review to objectively evaluate the diagnostic capabilities of SPECT/CT in this area. We conducted a systematic review of relevant electronic databases up to 30 August 2020. The outcomes of interest were the reporting of SPECT/CT to identify benign and malignant IBLs and the calculation of the sensitivity and specificity of the index test, based on histopathological examination or clinical and imaging follow-up as the reference standard. After the risk of bias and eligibility assessment, 12 articles were identified and synthesised in the meta-analysis. The pooled sensitivity and specificity of SPECT/CT for diagnosing IBLs are 93.0% [95% confidence interval (CI) 0.91-0.95] and 96.0% (95% CI 0.94-0.97), respectively. There was heterogeneity of the articles due to variable imaging protocols, duration of follow-up and scoring methods for interpreting the SPECT/CT results. The heterogeneity poses a challenge for accurate interpretation of the true diagnostic capability of SPECT/CT. In conclusion, targeted SPECT/CT improves the specificity of diagnosing bone metastases, but efforts need to be made to standardise the thresholds for SPECT/CT, methodology, as well as harmonising the reporting and interpretation criteria. We also make some recommendations for future works.